PELAKSANAAN PERJANJIAN SEWA MENYEWA KIOS PASAR PUSAT KOTA PADANG PANJANG BERDASARKAN PERATURAN WALIKOTA NOMOR 2 TAHUN 2018 TENTANG SISTEM DAN PROSEDUR PENGELOLAAN PASAR PUSAT KOTA PADANG PANJANG - Edi Wahyudi; Anggun Lestari Suryamizon; Mahlil Adriaman (Ensiklopedia of Journal, 2023)
The rental agreement is regulated in chapter VII of Book III of the Civil Code entitled "About Renting" which includes Articles 1548 to Article 1600 of the Civil Code. Rent in Dutch is called huurenverhuur and in English it is called rent or hire. leasing is an agreement between the lessee and the lessee. The lessee hands over the goods to be rented to the lessee to be fully enjoyed. The party who rents is not necessarily the owner of the goods or services that are leased to the lessee. The purpose of concluding a lease agreement is to grant usage rights to the lessee so that objects that are not in the status of property rights can be rented out by parties who have rights over these objects. One of the institutions that enters into rental agreements with kiosks or booths at the Central Market is the Marketing Office of the City of Padang Panjang, which has a role in implementing rental agreements with active traders in the City of Padang Panjang. Implementation of the lease agreement for renting a kiosk or booth in the central market of Padang Panjang City based on Mayor Regulation Number 2 of 2018 concerning Systems and Procedures for Management of the Padang Panjang City Central Market. Keywords: Agreements, Leases, Market Stalls.